2023
DOI: 10.1017/s0007114523000971
|View full text |Cite
|
Sign up to set email alerts
|

Estimated daily intake and health risk assessment of toxic elements in infant formulas

Abstract: In this study, the heavy metal (Al, Mn, Co, Cu, Zn, As, Se, Cd, Sn, Pb, and Hg) concentrations were determined in a total of 72 infant formula samples manufactured by 16 different brands in Türkiye. During the analyses, Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used in evaluating the nutritional profile and the toxicological risk associated with the consumption of these products. Given the analysis results, the highest Pb content was found in milk-based 'beginner’ formulas (0-6 months, 3 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…However, studies have reported that infant formula contains various levels of heavy metals (Elaridi et al, 2021;Sager et al, 2018;Traves, 2015) and that exposure to such heavy metals poses a threat to infant health (Başaran, 2022;Sipahi et al, 2014). Compared with adults, infants are more sensitive to toxic heavy metals because they absorb more contaminants and have a lower threshold for adverse health effects (Demir & Agaoglu, 2023;Eticha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have reported that infant formula contains various levels of heavy metals (Elaridi et al, 2021;Sager et al, 2018;Traves, 2015) and that exposure to such heavy metals poses a threat to infant health (Başaran, 2022;Sipahi et al, 2014). Compared with adults, infants are more sensitive to toxic heavy metals because they absorb more contaminants and have a lower threshold for adverse health effects (Demir & Agaoglu, 2023;Eticha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%